Analysis of orthophosphate phytoremediation from hotel detergent waste and its effect on increasing biomass in water hyacinth plants (Eichhornia Crassipes) - Febri Yanti; Anita Debora Simangunsong (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This research is motivated by the high levels of phosphate, which can be in the form of orthophosphate in the waters where most of it comes from hotel waste that contains detergents which are one of the factors of water pollution. The research aims to strive for an environmental mitigation engineering system to reduce or even eliminate pollution using a plant-based waste treatment technique known as phytoremediation. Phytoremediation uses water hyacinth, which utilizes water hyacinth plants as an adsorbent of waste containing phosphate in a medium. The phosphate levels in hotel detergent waste will be reduced before the waste is released into the waters of Lake Toba. The results of this study are that the pH and temperature are still following the parameters of the predetermined threshold; namely, the pH is around 6-9, and the temperature does not change. The average TSS test results decreased from the first, fourth, and seventh days to around 21. The average BOD test results did not meet the wastewater quality standard of more than 50 mg/liter. The average Orthophosphate test results increased so that the effect of water goiter to reduce pollution is not such a big impact, and the effect of the mass of water hyacinth before and after being put into the detergent waste decreased by an average of 3.75 grams.